Strategies to innovate in SMEs: analyzing the key factors of internationalization and interaction in Basque and Sicilian firms - Massimo Cermelli; Pier Francesco Asso; Vito Pipitone (European Regional Science Association (ERSA), 2013)
The increasing openness of economies and the phenomenon of globalization has led to know-how and innovation becoming the key factors for business in terms of competitiveness. Thus, the fact that the activities and services are increasingly innovative means that the construction of innovation is channeled through the social sphere, attributing an increasingly important and critical role to the field of local development. For this motive, in recent years, economic literature has focused its attention at the regional and local level. The liberalization of transport and the development of the information technologies have enabled traditional production factors, such as the availability of natural resources, low labor and capital costs, ceasing to be a real competitive advantage for territories. The economy begins to distance from market factors such as contractual relations becoming more relational and especially focusing attention on geographical context conditions capable of promoting interaction between individual and collective subjects. The knowledge of workers becomes, within firms, the raw material from which the company can get innovative products and services. The exchange of knowledge and experiences between firms and within firms together with a high level of interaction among the agents, that constitute the social and economic environment of a region, becomes a source of competitive advantage and represent a key strategy for the generation of innovation at the firm levels. Internationalization and interaction for SMEs represent action strategies in an increasingly complex environment where territory plays a key role. The geographical areas with all their knowledge and experiences present in their context are the source of tacit knowledge that determines the competitive advantage of the new millennium. In this paper we analyze the predictors of innovation generation in SMEs, demonstrating the relevance of internationalization and cooperation strategies in Basque and Sicilian firms comparing the two experiences. SMEs constitute the majority productive Basque and Sicilian territorial reality and their impact on the local economy is crucial for the development of the two regions.
Keywords: O31; O32; 330